The importance and challenges of primary chicken embryo liver cells in studies of poultry viral diseases: a review - Mohamed Sohaimi, Norfitriah; Clifford, Ugwu Chidozie (Scienceline Publication, 2023)
Primary chicken embryo liver (CEL) cells are derived from the liver tissue of chicken embryonated eggs (CEE) using an aseptic isolation technique and growth under a controlled atmosphere in an artificial environment for cell attachment and proliferation. Although this primary cultured cell has been established for more than six decades, utilization of primary cells is still the preferable medium nowadays as the “gold standard” due to several advantages over other diagnostic techniques. Cells provide better adaptability of the viruses and easily mimic the natural host environment with high virus titration. The volume of virus suspension could be increased by applying an immortal chicken embryo liver-derived cell line. The current review aimed to highlight the importance and challenges of using primary chicken embryo liver cells in poultry virus studies. Primary CEL cells are widely used as an alternative host for diagnosis of infectious poultry viruses, cultivation and passaging of virus isolates, and vaccine production. Yet, there are some challenges and limitations in handling this primary cell, which requires appropriate facilities and environment to sustain the rapid growth of confluent monolayer cells, as highlighted in this paper. The availability of specific pathogen-free CEE is a major concern due to limited resources globally, thus creating a challenge for vaccine manufacturers to upscale the cultured cells. Future improvement of primary cell culture preparation necessitates new technology by applying cellular microcarrier in the bioreactor machine for efficient cell growth and subsequent routine virus cultivation. This study can help the researchers understand the advantages of primary CEL cells and their applications due to their significant impact on poultry viruses.